Physical Activity and Health Beliefs among Saudi Women - Einas S. Al-Eisa; Hana I. Al-Sobayel (Journal of Nutrition and Metabolism)
Background. Physical activity (PA) is associated with health benefits and disease prevention and is often prescribed in managing many health conditions. Understanding the cultural influences is relevant in order to effectively promote PA. The objective of this study was to assess the level of PA among Saudi women, measured by daily step count, and the association between PA and health beliefs. Methods. A total of 161 eligible participants were asked to complete two questionnaires to assess health beliefs: Health Locus of Control (HLC) and Self-Efficacy Assessment Scale. Each participant was given a pedometer and a diary to record their daily PA for two weeks. Results. One hundred and five participants completed the two weeks pedometer data (mean age 26.3±7.1 years, BMI 25±4.2 kg/m2). The average pedometer score over two weeks was 5114±2213 steps. Step count had strong correlation with self-efficacy (rs=0.75), mild correlation with internal HLC (rs=0.42), and mild negative correlation with external HLC (rs=−0.35). Conclusion. The study demonstrates high level of inactivity among Saudi females in reference to the international recommendation for minimum activity. The data also reveal an association between PA and health beliefs. Ultimately, such information can be used to design gender- and culture-sensitive interventions that could enhance adherence to PA.